THE PROBLEMS OF ENGINEERING GEOLOGICAL SURVEYING FOR RECONSTRUCTION GROUND OF CIVIL BUILDINGS - KOSTIUCHENKO, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The problems of building specifications and features of engineering geological surveying researches for the reconstruction basis and operational reliability of buildings of considered. It is recommended to improve the ongoing specifications by additional studying and reliability of buildings experience, because these problems of important practical, scientific and psychological aspects.